(untitled) (The Research of Medical Science Review, 2025)
This study assessed the therapeutic efficacy of three antiprotozoal agents—Imidocarb dipropionate, Diminazen aceturate, and Buparvaquone—for treating tick-borne protozoal infections (anaplasmosis, babesiosis, theileriosis, and mixed infections) in buffaloes under field conditions in Sindh, Pakistan. Thirty-eight clinically infected buffaloes were divided into five groups based on diagnosis: anaplasmosis (n=5), babesiosis (n=10), theileriosis (n=8), mixed infections (n=5), and untreated controls (n=10). Diagnosis was confirmed through microscopy. Imidocarb dipropionate resulted in significant parasitemia reduction and full recovery in both anaplasmosis and mixed infection groups. Diminazen aceturate showed strong efficacy against babesiosis, while Buparvaquone provided limited response against theileriosis, with two animals succumbing to advanced disease. The control group exhibited worsening clinical signs and progression of disease over 15 days. These results suggest Imidocarb and Diminazene are effective treatments for anaplasmosis and babesiosis, respectively. Buparvaquone's efficacy appears to depend on early intervention. The study underscores the importance of timely diagnosis and targeted treatment, supporting WHO and OIE guidelines for managing protozoal infections in bovines.